PERJUANGAN PEREMPUAN MERAIH KEMANDIRIAN DALAM RUANG SOSIAL STUDI ATAS NOVEL MIDAH SIMANIS BERGIGI EMAS KARYA PRAMODYA ANANTA TOER - M. Imam Sofyan Yahya (Universitas Negeri Makassar, 2016)
Abstract. The struggle of women gain independence in the social space studies on novel Midah simanis gold teeth Pramodya work Ananta Toer. This article analyzes the novel Midah Simanis Gold Teeth by Pramoedya Ananta Toer using elements of narrative theory and the concept of Pierre Bourdieu on social room, arena, capital, habitus and distinction, discusses the process of Midah leaders struggle to achieve independence in the social space. The results showed that although Midah received discriminatory treatment in the social space, both private and public, he was able to perform a variety of operations and strategies by optimizing and developing its capitals to achieve success and independence of life.